Experimental investigation of the effect of the ballast/sleeper interventions on railway track performance - Safari Baghsorkhi, Mohammad (2017)
Railways are integral to the transportation system of a growing economy. There is a constant demand by numerous stakeholders of the railway industry for greater train operational speeds, tonnage, passenger comfort and safety with minimal service disruptions. This is partly achievable through the improvement of the main components of railway track. A fundamental requirement for any railway track is to be able to maintain its as-built geometry over its service life. Settlement of a ballasted railway track is mainly caused by cyclic loading due to the passage of traffic. To return the rail track to the as-built alignment and level, track maintenance needs to be carried out. Tamping is one of the most common and traditional ways of maintaining the track and is not only costly but causes interruption to the day-to-day operations and damages the long term performance of the ballasted track. It therefore remains important to policy makers, rail practitioners and researchers to identify new techniques, innovations or processes that will prolong intervals between scheduled track maintenance. Track settlement is influenced by several interrelated track variables, not least of which are the railway sleeper, ballast and ballast-sleeper interface that have potential for alteration to be optimised with respect to the track performance. In this research, results are presented from a parametric experimental study using three different apparatus namely box test (confined), Composite Element Test (CET) (semi-confined), and Railway Test Facility (RTF) (full-scale), to investigate performance of different sleeper and ballast configurations. The box test and the CET apparatus were used ahead of the RTF (full-scale) apparatus as preliminary tests to obtain an insight into the performance and potential benefits of different sleeper types with and without the use of Under Sleeper Pads (USPs). The aforementioned apparatus were also used for comparison with the full-scale apparatus to assess the consistency of the sleeper settlement results (phase 1 tests). The purpose of using the box test and CET apparatus was also to allow a relatively large number of simplified tests to be carried out on sleeper and ballast combinations (Phase 2 tests) within a reasonable cost and time frame. Phase 2 tests were designed and conducted with consideration of the phase 1 test results. The test results from phase 1 showed that increasing the number of contact points between ballast particles and sleeper, and increasing the coefficient of friction at ballast-sleeper interface improved the settlement performance of the tarckbed. Therefore, having this in mind, further tests were designed and conducted including: finer ballast grading, two-layered ballast systems, frictional sleepers and USPs, and USP types with various stiffnesses. In addition, further tests on ballast bonding/gluing and ballast reinforcement were conducted with the aim of investigating possible ways of minimising ballast bed deterioration. Application of ballast gluing was proven beneficial (in literature) in improving ballast bed performance, however, the overall cost of super glues used for this method was high. Therefore in this study, a low cost glue was introduced and its performance was tested under conditions similar to real track. With regard to ballast reinforcement, the expanded polystyrene was added to the ballast sample with the aim of decreasing the contact forces between ballast particles and consequently minimising ballast bed deterioration and settlement. The observations in this study sought to establish qualitative and quantitative data on the effects of different parameters on the track performance, which may lead to a longer service life with less maintenance. The results showed that the type of sleeper has an influence on the performance of a railway track. With respect to settlement performance of a railway track, sleepers with higher depth and width, coefficient friction, and bending stiffness performed better. Out of all investigated sleeper types without any additional interventions, concrete mono-block gave the least settlement and the plastic sleeper gave the most. It was also found that inclusion of USPs (regardless of type) can be beneficial compared to the ‘no USP’ scenario in: (1) Increasing trackbed resiliency. (2) Reducing maintenance works related to settlement. (3) Reducing sleeper deflections (hogging) at the middle of sleeper. (4) Reducing the rate of deterioration of sleeper support at the rail seat (6) Reducing differences in the performance of different sleeper types. (7) Reducing tendency towards centre binding. (8) Reducing transmitted pressure on subgrade. (9) Making the trackbed stiffness more uniform. The conclusion of research was that use of concrete mono-block sleeper, USPs, finer ballast grading, a two-layered ballast system with finer ballast grading on top, frictional sleeper, frictional USP, and ballast gluing all have potential to improve the performance of ballasted railway track and reduce the maintenance requirements.